(untitled) (Research, Society and Development, 2020)
In this study, the objective is to reflect on the initial and continuing education of teachers, the knowledge and teaching practices, with a focus on Youth and Adult Education (EJA). The methodology is qualitative based on bibliographic and documentary research. The text discusses the conceptions of teacher training, knowledge and teaching practices that, in a way, dialogue with the modality. In addition, it retrieves relevant facts to compose a brief history and legal support about the initial and continuing teacher training designed for the referred modality, so that we can glimpse the weaknesses and advances in the national and local contexts. It could be inferred that the initial training of teachers, in the EJA modality, is in contraction, being only offered in the form of a discipline in the degrees of Pedagogy. In addition, EJA is marked by specificities and, therefore, the continuing education processes constitute the possible spaces for teacher reflection and innovation in practices to qualify and give meaning to teaching for young people and adults.